Characterizing community courts. (18th September 2017) - Gal, Tali; Dancig‐Rosenberg, Hadar
Abstract: Community courts (CCs) provide a therapeutic diversion for repeat low‐level offenders. This article explores the characteristics of two Israeli CCs using the Criminal Law Taxonomy (CLT), an instrument developed by the authors for assessing process‐, stakeholder‐, substance‐, and outcomes‐related characteristics of criminal justice mechanisms. Through court‐hearing observations and a process of multi‐rater coding of cases, the article analyzes the courtroom dynamics according to a set of 13 measurable parameters. The process was conceived as a vehicle for promoting the model goals: it was highly offender‐oriented and involved a needs‐based terminology while allowing for restrained expression of emotion. However, the process included no victim–offender dialogue and offender supporters and community representatives were only partially involved. The findings provide information about the program's implementation integrity; they also offer a basis for comparison with the characteristics of other justice mechanisms. While focusing on an Israeli program, the issues the article addresses reflect practices and controversies that are salient in many jurisdictions worldwide.